Digital holography and wavefront sensing principles, techniques and applications - Schnars, Ulf; Falldorf, Claas; Watson, John; Juptner, Werner; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2015)
This book presents a self-contained treatment of the principles and major applications of digital hologram recording and numerical reconstruction (Digital Holography). This second edition has been significantly revised and enlarged. The authors have extended the chapter on Digital Holographic Microscopy to incorporate new sections on particle sizing, particle image velocimetry and underwater holography. A new chapter now deals comprehensively and extensively with computational wave field sensing. These techniques represent a fascinating alternative to standard interferometry and Digital Holography. They enable wave field sensing without the requirement of a particular reference wave, thus allowing the use of low brilliance light sources and even liquid-crystal displays (LCD) for interferometric applications.
Introduction -- Fundamental Principles of Holography -- Digital Holography -- Digital Holographic Interferometry (DHI) -- Digital Holographic Particle Sizing and Microscopy -- Special Techniques -- Computational Wave Field Sensing -- Speckle Metrology.
Electronic reproduction.
Keywords: Holography -- Data processing; Image processing -- Digital techniques; Optical detectors